RADIOACTIVITY, HEAVY METAL AND OXIDATIVE STRESS MEASUREMENTS IN THE FOLLICULAR FLUIDS OF CATTLE BRED NEAR A COAL-FIRED POWER PLANT - Akarsu, S. A.; Yilmaz, M.; Niksarlioglu, S.; Kulahci, F.; Risvanli, A. (Pakistan Agricultural Scientists Forum, 2017)
Coal-fired power plants release heavy metals via gas and dust discharges and can radioactive pollution. This can harm human and animal health. Livestock are often exposed, and the reproductive system is one of the most commonly affected systems. In this study, we measured heavy metals and radioactivity levels as well as oxidative stress parameters in the ovarian follicular fluids from cattle bred near coal-fired power plants. Samples were from the slaughter houses near the coal-fired power plants in Elbistan (n=25) samples from Elazig (n=14)-300 km from the plant-served as the control. Cadmium (Cd), lead (Pb), and mercury (Hg) measurements were performed using atomic absorption spectrophotometry. Malondialdehyde (MDA), Glutathione (GSH), and Glutathione Peroxidase (GSH-Px) levels were measured colorimetrically with a spectrophotometer. Pb-210, I-129, U-238, Th-232 and K-40 were measured with a gamma counter. It was conclude that the Pb concentration was high in the follicular fluids of the cattle bred near the Elbistan coal-fired power plant (22.27 +/- 1.73 mu g/dL, P < 0.05). However, MDA concentration was high in the cattle from Elazig (85.77 +/- 10.40 mu mol, P < 0.05). The Cd, Hg, GSH levels and GSH-Px activity were not different (P > 0.05). No difference was found between the groups with regard to radioactivity parameters. These assays may be of value to animal breeders and authorities working near the Elbistan Power Plant.
Keywords: Cattle; follicular fluid; radioactivity; oxidative stress; heavy metals